2015
DOI: 10.1111/rec.12167
|View full text |Cite
|
Sign up to set email alerts
|

Biomass harvest of invasive Typha promotes plant diversity in a Great Lakes coastal wetland

Abstract: Ecological and financial constraints limit restoration efforts, preventing the achievement of desired ecological outcomes. Harvesting invasive plant biomass for bioenergy has the potential to reduce feedback mechanisms that sustain invasion, while alleviating financial limitations. Typha × glauca is a highly productive invasive wetland plant that reduces plant diversity, alters ecological functioning, its impacts increase with time, and is a suitable feedstock for bioenergy. We sought to determine ecological e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 40 publications
2
56
0
Order By: Relevance
“…Although harvesting biomass increased light penetration to the soil surface in the first growing season, we did not observe enhanced native plant density or biomass relative to controls, possibly indicating depauperate seed banks within the mesocosm soils. In a northern Michigan field experiment however, harvest of aboveground Typha biomass increased native plant diversity and richness for at least 2 years relative to unmanipulated controls (Lishawa et al 2015), and resulted in greater plant richness than mowing (Lawrence et al unpublished data). Hall et al (2008) also observed greater plant richness and diversity with harvest of T. dominegensis in central Mexican wetlands compared with unmanipulated controls.…”
Section: Mechanical Harvest Of Typha Biomassmentioning
confidence: 97%
See 2 more Smart Citations
“…Although harvesting biomass increased light penetration to the soil surface in the first growing season, we did not observe enhanced native plant density or biomass relative to controls, possibly indicating depauperate seed banks within the mesocosm soils. In a northern Michigan field experiment however, harvest of aboveground Typha biomass increased native plant diversity and richness for at least 2 years relative to unmanipulated controls (Lishawa et al 2015), and resulted in greater plant richness than mowing (Lawrence et al unpublished data). Hall et al (2008) also observed greater plant richness and diversity with harvest of T. dominegensis in central Mexican wetlands compared with unmanipulated controls.…”
Section: Mechanical Harvest Of Typha Biomassmentioning
confidence: 97%
“…For example, assuming similar N and P content of leaf and litter biomass that we measured in the current study (%N = 0.9 %, %P = 0.2 %), a one-time harvest of Typha-invaded portions (16 ha) of Cheboygan Marsh in northern Michigan (USA) would remove approximately 4100 kg of N and 910 kg of P (assuming 2846 g dry biomass/m 2 ; Lishawa et al 2015), helping achieve pollutant load reduction goals of nutrient-impaired Lake Huron. Similarly, Boyd et al (2015) quantified biomass and leaf nutrient content of a Phragmites-invaded wetland in central Florida and estimated that biomass harvest would address *25 % of Lake Jesup's pollutant load reduction goal.…”
Section: Mechanical Harvest Of Typha Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…dominance (Mulhouse and Galatowitsch, 2003; Hall and Zedler, 2010) due to relatively short term seed viability (van der Valk et al, 1999) and high light requirements for germination (Kettenring et al, 2006). Further, Lishawa et al (2015) found that in a northern Great Lakes coastal wetland, Carex spp. diversity and abundance took 2 years following Typha biomass removal to increase from pre-treatment levels.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was further illustrated by the response of Juncus nodosus and J. alpinoarticulatus, which were indicator species significantly associated with harvesting in wet meadow plots. In the emergent marsh, cutting biomass below standing water (all treatments) effectively reduced Typha abundance, likely by preventing aeration and causing rhizome mortality (Jordan & Whigham, 1988;Murkin & Ward, 1980 (Lishawa et al, 2015). are prolific in GL coastal wetland seed banks (Keddy & Reznicek, 1986), and these early seral species can become the dominant emergent plants following water-level reduction and mudflat exposure (Tuchman unpublished), but they quickly disappear from the emergent community with succession or Typha invasion (Larkin et al, 2012;Tuchman et al, 2009).…”
Section: Taxonomic and Phylogenetic Diversity Responses To Restoratmentioning
confidence: 99%